2012
DOI: 10.1007/s00707-012-0634-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural health monitoring of cylindrical structures using guided ultrasonic waves

Abstract: The research field of structural health monitoring (SHM) in the realm of civil engineering has emerged rapidly. SHM concepts are based on integrated sensors and actuators to evaluate the structural state. Beside common structural response methods and other nondestructive testing techniques, wave-based ultrasonic techniques are widely used especially because of their flexibility. Monitoring cable structures such as overhead transmission lines or stay cables in suspension bridges is one objective of those wave-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…[9][10][11] Ultrasonic guided waves (GWs) are a promising alternative to current SHM techniques, because a large area can be scanned with fewer sensors, and damages that are located in inaccessible areas can be detected; 12,13 GW propagation in steel bars has been extensively studied to detect such damages. 14 The signal strength and time-of-flight measurements of GWs have indicated the potential in assessing the changes in rebar diameter. 15 Studies have also indicated that the pitting type of corrosion can be quantified using GWs.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Ultrasonic guided waves (GWs) are a promising alternative to current SHM techniques, because a large area can be scanned with fewer sensors, and damages that are located in inaccessible areas can be detected; 12,13 GW propagation in steel bars has been extensively studied to detect such damages. 14 The signal strength and time-of-flight measurements of GWs have indicated the potential in assessing the changes in rebar diameter. 15 Studies have also indicated that the pitting type of corrosion can be quantified using GWs.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of methods have been developed for the efficient detection of cracks on cylinders, such as optical fibers [5], electrical resistance [6], vibration detection [7], magnetic induction [8], infrared thermography [9], and ultrasound testing [10][11][12][13]. Among them, the ultrasound testing technique has been widely used due to its relatively high spatial resolution, portable operation, high performance ratio, and high effectiveness in damage detection.…”
Section: Of 18mentioning
confidence: 99%
“…This mode conversion is quantified in terms of reflection and transmission, or, scattering coefficients. Gaul et al [51] analyzed reflection and transmission of guided waves at arbitrarily shaped discontinuities in the cylinders using finite element and boundary element methods. The numerical results were confirmed with a series of laser-based ultrasound measurements.…”
Section: Monitoring Pitting Corrosionmentioning
confidence: 99%